Civilisation week - Tuan Sidek, T. M. (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
2-10 Oct 2009. More than 1000 students who registered for Islamic and Asian Civilizations course (TITAS) worked hand in hand to ensure the Civilization Week programme was a success.